2013
DOI: 10.1126/scitranslmed.3005271
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Prevents Seizures After Depletion of STRADA in a Rare Neurodevelopmental Disorder

Abstract: A rare neurodevelopmental disorder in the Old Order Mennonite population called PMSE (polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome; also called Pretzel syndrome) is characterized by infantile-onset epilepsy, neurocognitive delay, craniofacial dysmorphism, and histopathological evidence of heterotopic neurons in subcortical white matter and subependymal regions. PMSE is caused by a homozygous deletion of exons 9 to 13 of the LYK5/STRADA gene, which encodes the pseudokinase STRADA, an upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 33 publications
2
99
0
Order By: Relevance
“…Treatment with the mTOR inhibitor rapamycin in both the mouse model and cell lines rescued the phenotype caused by loss of STRADA. These preclinical data led to a small open trial of rapamycin (sirolimus in clinical parlance) in five PS children for 8 months to 4 years, which showed prevention of seizures in these patients (Parker et al 2013). This was the first study to show epilepsy prevention with an mTOR inhibitor and suggested that early treatment could dramatically alter clinical seizure onset.…”
Section: Pretzel Syndrome: a Recessive Mtoropathymentioning
confidence: 98%
See 2 more Smart Citations
“…Treatment with the mTOR inhibitor rapamycin in both the mouse model and cell lines rescued the phenotype caused by loss of STRADA. These preclinical data led to a small open trial of rapamycin (sirolimus in clinical parlance) in five PS children for 8 months to 4 years, which showed prevention of seizures in these patients (Parker et al 2013). This was the first study to show epilepsy prevention with an mTOR inhibitor and suggested that early treatment could dramatically alter clinical seizure onset.…”
Section: Pretzel Syndrome: a Recessive Mtoropathymentioning
confidence: 98%
“…PS postmortem brain tissue contains enlarged dysmorphic neurons as well as heterotopic neurons within the subcortical white matter show numerous phospho-S6-and phospho-p70S6-kinase-labeled neurons, similar to FCDIIB and tubers. STRADA shRNA knockdown in vivo in fetal mouse brain induces mTORC1 activation, neuronal enlargement, laminar disorganization, and subcortical white matter heterotopias similar to human PS (Orlova et al 2010a ;Parker et al 2013). Furthermore, there are severe impairments in cell motility, directionality, and polarity in mouse neural progenitor cells lacking STRADA (Orlova et al 2010a;Parker et al 2013).…”
Section: Pretzel Syndrome: a Recessive Mtoropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Genes responsible for regulation of mTORC1 have been identified in epileptic patients with isolated focal cortical dysplasia IIb, 30,31 hemimegencephaly, 32 and syndromic epilepsies caused by DEPDEC5, 32,33 PTEN, 34 and STRADA. 35 Loss of mTORC1 regulation has been identified in animal models of acquired epilepsies, including temporal lobe epilepsy and posttraumatic epilepsy, which are responsive to sirolimus treatment. 36,37 Human patients with early-onset intractable epilepsy caused by STRADA mutation demonstrate marked reduction in seizure frequency when treated with sirolimus.…”
Section: Classification Of Evidence This Interventional Study Providesmentioning
confidence: 99%
“…36,37 Human patients with early-onset intractable epilepsy caused by STRADA mutation demonstrate marked reduction in seizure frequency when treated with sirolimus. 35 Thus targeting the mTOR pathway with mTORC1 inhibitors such as everolimus may have application well beyond epilepsy associated solely with TSC.…”
Section: Classification Of Evidence This Interventional Study Providesmentioning
confidence: 99%